miR-140-5p suppresses retinoblastoma cell proliferation, migration, and invasion by targeting CEMIP and CADM3 - Miao, Xiaolin; Wang, Zhen; Chen, Bingyu; Chen, Yiqi; Wang, Xi; Jiang, Luxi; Jiang, Shanshan; Hao, Ke; Zhang, Wei (Cellular and Molecular Biology, 2018)
Retinoblastoma (RB) is a childhood intraocular tumor, affecting millions of patients worldwide. MicroRNA-140-5p (miR-140-5p) was demonstrated to be involved in the tumorigenesis of various human cancers; however, its role in RB remains undetermined. In this study, quantitative real-time PCR (qRT-PCR) and Western blot assays were used to determine the expression levels of miR-140-5p, cell migration-inducing protein (CEMIP), and cell adhesion molecule 3 (CADM3) in RB tissues and cell-lines. The proliferation ability was detected by cell-counting kit 8 (CCK-8), Edu staining, and colony formation assay. The cell cycle and migration and invasion abilities were measured by flow cytometry, wound-healing assay and Transwell assays, respectively. The correlation between miR-140-5p and CEMIP/CADM3 were then confirmed by immunofluorescence (IF) and dual-luciferase reporter assays. The results showed that miR-140-5p expression was significantly decreased; however, CEMIP and CADM3 expression was increased in RB tissues and cells. Overexpression of miR-140-5p inhibited proliferation, migration, and invasion of RB cells. We also found that miR-140-5p inhibited CEMIP and CADM3 expressions in RB cells. In addition, we demonstrated that miR-140-5p might negatively regulate the transcriptional activities of CEMIP and CADM3 by targeting their 3'-UTR. Therefore, we suggested that miR-140-5p could be a potential therapeutic target for the treatment of RB through CEMIP and CADM3.